Beban Kerja Obyektif Tenaga Perawat di Pelayanan Rawat Inap Rumah Sakit - Rohmat Dwi Romadhoni; Widodo J. Pudjirahardjo (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2016)
Inpatient services at the X Hospital consists of Intensive Care Units and Inpatient Units. In 2014, a nurse  at the unit as a whole experienced a shortfall of 66.67% from 9 rooms there. This shortage triggered theincreasing of nurse workload. This study aimed to find out the objective workload on nurses in Intensive Care Units and Inpatient Units. This research is quantitative descriptive with cross-sectional design. The sample used is total sampling, as many as 174 nurses. Data obtained using activity sheets time and motion study indirectly (self-assessment). Results from this study show the objective workload in the Intensive Care Unit on the morningshift have a heavy workload category, afternoon shift and the night shift has a moderate workload category, while at Inpatient Unit on the morning shift and afternoon shift has a heavy workload category, and shift night has amoderate workload category. The conclusion of this study is objective workload in the Intensive Care Unit has a moderate workload category, while the objective workload in the Inpatient Unit has a heavy workload category.Keywords: nurse,objective workload, time and motion study